2009
DOI: 10.1063/1.3263733
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar resistive switching in individual Au–NiO–Au segmented nanowires

Abstract: Articles you may be interested inElectric field manipulation of nonvolatile magnetization in Au/NiO/Pt heterostructure with resistive switching effect Appl. Phys. Lett.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 30 publications
1
36
0
1
Order By: Relevance
“…Unlike template-free methods, the templateassisted synthesis used here can produce a very large number of nearly identical, high-definition heterojunction MOM nanowires that do not require sorting. 23,24 After extensive heat treatment analysis, it is found that the nanowires annealed at 225 C for 20 h in a controlled atmosphere, 5% H 2 (balance N 2 ) with a 20 sccm flow successfully yielded the Au-Fe 3 O 4 -Au segment. With the above controlled oxidation conditions, Fe segment directly transformed into Fe 3 O 4 .…”
Section: -mentioning
confidence: 99%
See 3 more Smart Citations
“…Unlike template-free methods, the templateassisted synthesis used here can produce a very large number of nearly identical, high-definition heterojunction MOM nanowires that do not require sorting. 23,24 After extensive heat treatment analysis, it is found that the nanowires annealed at 225 C for 20 h in a controlled atmosphere, 5% H 2 (balance N 2 ) with a 20 sccm flow successfully yielded the Au-Fe 3 O 4 -Au segment. With the above controlled oxidation conditions, Fe segment directly transformed into Fe 3 O 4 .…”
Section: -mentioning
confidence: 99%
“…23 The inset of Figure 5 shows the low magnification optical micrographs of a typical single MOM nanowire device thus fabricated with the functional Fe 3 O 4 segment with $250 nm thickness and 500 nm in length. Note that the Fe 3 O 4 segment of the MOM nanowire is not attached to the substrate mechanically, and the metal nanowires provide no mechanical constraint, hence no substrate-induced strain is expected in the Fe 3 O 4 segment.…”
Section: -mentioning
confidence: 99%
See 2 more Smart Citations
“…Various metal oxides and perovskites have been actively studied as a material for ReRAM [1][2][3][4][5][6][7][8][9]. A metal oxide or perovskite layer, which exhibits resistive switching (RS) phenomenon, is sandwiched between two metal electrodes.…”
Section: Introductionmentioning
confidence: 99%